2004
DOI: 10.1023/b:brea.0000032919.83803.48
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic and Predictive Impact of the HER-2/neu Extracellular Domain (ECD) in the Serum of Patients Treated with Chemotherapy for Metastatic Breast Cancer

Abstract: In our group of metastatic breast cancer patients, elevated HER-2/neu ECD levels are associated with decreased overall survival. With regard to progression-free survival, particularly patients with high HER-2/neu ECD levels seem to benefit from taxane-containing chemotherapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
104
2
6

Year Published

2006
2006
2017
2017

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(129 citation statements)
references
References 21 publications
17
104
2
6
Order By: Relevance
“…However, data interpretation is limited by the small sample and the absence of objective responses. Furthermore, although elevated HER2 ECD has been reported to be associated with poorer outcome, it has not been clearly related to response to therapy (22,23). This is the first study involving the selective HER2 kinase inhibitor CP-724,714.…”
Section: Discussionmentioning
confidence: 99%
“…However, data interpretation is limited by the small sample and the absence of objective responses. Furthermore, although elevated HER2 ECD has been reported to be associated with poorer outcome, it has not been clearly related to response to therapy (22,23). This is the first study involving the selective HER2 kinase inhibitor CP-724,714.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, no morphological analysis of the detected tumour cells is possible (6) a heterogeneous expression of target genes might lead to a non-accurate enumeration of tumour cells, and many transcripts are expressed at low levels in normal blood cells (97,98), leading to false-positive results, which makes the selection of target genes a crucial point in this experimental approach. Therefore, a stringent quality control has to be applied during the whole procedure, including use of reference guidelines, positive and negative controls, optimal sample quality and primer selection, adequate instrument care, and analytical sensitivity and specificity (99)(100)(101)(102)(103). If all of these steps are conducted carefully, reliable quantitative data can be obtained, which could in term lead to a personalized medicine (97), and even further: a detection of CTCs in early stage cancer could influence the application of different treatment options (104,105).…”
Section: Ctc Detectionmentioning
confidence: 99%
“…It has been reported that trastuzumab inhibits Her2 extracellular domain cleavage; this is important considering that the remaining cleaved HER2 receptor is constitutively activated (46,47), suggesting that the detection of sHer2 also reflects a biologic process leading to a more aggressive tumour behavior (48). Elevated levels of sHer2 have been observed in patients with primary (49) or metastatic breast cancer (50,51). As detailed below in the specific biomarker section (E.3), there are some studies to suggest that elevated serum Her2 levels are a negative prognostic and predictive factor.…”
Section: A Biomarkers In Breast Cancermentioning
confidence: 99%